2018
DOI: 10.3390/v10070344
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Changes in Sogatella furcifera under Southern rice black-streaked dwarf virus Infection and Temperature Stress

Abstract: Southern rice black-streaked dwarf virus (SRBSDV) is a devastating newly emerged rice reovirus in Eastern and Southeastern Asia transmitted by a long-distance migratory pest, the white-backed planthopper (WBPH). We previously showed that SRBSDV infection decreased the cold tolerance but improved the heat tolerance of its vector, WBPH. Comparative metabolomic analysis was used to explore the potential mechanisms underlying these changes in temperature stress response. Fourth-generation WBPH nymphs were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(64 reference statements)
1
5
0
1
Order By: Relevance
“…The presence of BLRV and PEMV1 increased myristic acid amount in A. fabae and A. pisum , respectively. These results are in accordance with the study which indicated that FAs like myristic acid were increased in V planthopper vector ( Sogatella furcifera (Horváth) [Hemiptera: Delphacidae]) infected with Southern rice black‐streaked dwarf virus ( Reoviridae : Fijivirus ) (Zhang et al., 2018). Viruses may manipulate the FA content in virus‐infected insects to provide the needed energy for immune defence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The presence of BLRV and PEMV1 increased myristic acid amount in A. fabae and A. pisum , respectively. These results are in accordance with the study which indicated that FAs like myristic acid were increased in V planthopper vector ( Sogatella furcifera (Horváth) [Hemiptera: Delphacidae]) infected with Southern rice black‐streaked dwarf virus ( Reoviridae : Fijivirus ) (Zhang et al., 2018). Viruses may manipulate the FA content in virus‐infected insects to provide the needed energy for immune defence.…”
Section: Discussionsupporting
confidence: 91%
“…[Hemiptera: Delphacidae]) infected with Southern rice black-streaked dwarf virus (Reoviridae: Fijivirus) (Zhang et al, 2018). Viruses may manipulate the FA content in virus-infected insects to provide the needed energy for immune defence.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, omics technology is increasingly being used to understand intricate biological systems and reveal the molecular characteristics behind complex cellular phenotypes [17,18]. Applications of omics platforms include the identification of genes (genomics), messenger RNA (mRNA, transcriptomics), proteins (proteomics), and metabolites (metabolomics).…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed nuanced expression of heat shock proteins in insects exposed to SRBSDV and heat stress, which may be due to the crosstalk between heat stress and antiviral pathways, both of which would be activated under this dual stress and potentially repressed by viral counterdefense strategies. In a follow-up metabolomics study of S. furcifera exposed to the same virus and environmental stressors, there was up-regulation of polyols and sugars in viruliferous planthoppers under both heat and cold stress, and up-regulation of certain amino acids, such as methionine, proline, threonine, ornithine, L-homoserine and β-alanine, under heat stress (Zhang et al, 2018). These same amino acids were down-regulated in response to cold stress.…”
Section: Vector Manipulation By Plant Viruses: a Direct Strategy For Promoting Vector Transmissionmentioning
confidence: 99%